UJI KEMAMPUAN PARASITIK JAMUR LECANICILLIUM LECANII TERHADAP MORTALITAS SISTA NEMATODA SISTA KUNING (GLOBODERA ROSTOCHIENSIS W.) - NOHAN REMBULAN, SOLICHAH Nohan (LenteraBio: Berkala Ilmiah Biologi, 2013)
Golden Cyst Nematode is one of the nematode Tylenchida ordo with Heteroderidae family destructive and deadly plant potatoes in large numbers in cycles cyst. It can reduce potato crop productivity. Therefore, it is necessary to apply biological control (IPM) to control cyst Golden Cyst Nematode, one which is to use biological agents. One of those attempt is by using entomopatogenic fungi, for example is Lecanicillium lecani. This research is a preliminary study which aims to determine the ability of parasitic fungus L. lecanii against cyst of Golden Cyst Nematode at various concentrations in laboratory scale. This research was experimental type using Completely Randomized Design (CRD) with one treatment factor. The treatment factor was the concentration of L. lecanii, which consisted of 2 concentrations. They were 107 spores/ml108 spores/ml, and control (no fungus L. lecanii conidia) was repeated 6 times replications for a total of 18 experiment units. Each treatment unit used 10 cyst of Golden Cyst Nematode. The data obtained were the amounts of cyst mortality of Golden Cyst Nematode. It was observed until 2 weeks or the cyst of Golden Cyst Nematode covered by fungi. The data were analyzed by probit regression analysis using SPSS 16.0 for windows to get the percentage mortality of cyst of Golden Cyst Nematode and to know the LD80. Based on the results of the study, it can be concluded that the effectiveness of the parasitic fungus L. lecanii causing mortality cyst of Golden Cyst Nematode at concentration 108 conidia/ml.. The value of LD80 was get at concentration 1,4 x 108 spores/ml.